The Effectiveness of the 30˚ Head Up Technique for Ineffective of Cerebral Tissue Perfusion in Meningitis Client - Rahmasuli, Resa; Putri , Nendela Resta Angga; Gunawan, Asep; Hidayat, Nur (KIAN JOURNAL, 2023)
Objective: This case study aims to gain direct experience in providing nursing care to children with meningitis with ineffective cerebral tissue perfusion problems. Methods: This study uses a descriptive case study design with a nursing approach. The subject in this research is An. S with meningitis who experienced cerebral tissue perfusion with data collection techniques including interviews, observation, physical examination, and documentation. Results: The results obtained after completing the nursing process include assessment, diagnosis, intervention, implementation, and evaluation within 4 days from 25-30 May 2022. The 30o Head Up Technique to increase awareness and maximize oxygenation to the brain in meningitis patients with deep breathing results normal limits and increased consciousness. Conclusion: Conclusions from Nursing Care of Meningitis Children with brain tissue perfusion problems. With the intervention of the Head Up 30o position technique, it is very effective to increase awareness and avoid recurring seizures.